Cree materials, Frank G. Speck Papers - Downes, P. G. (Prentice Gilbert), 1909-; Hallowell, A. Irving (Alfred Irving), 1892-1974; Schaeffer, Claude E.; Speck, Frank G. (Frank Gouldsmith), 1881-1950; Wallace, Paul A. W. (1911)
The Cree material in the Frank Speck papers are scattered around multiple sections of the finding aid, mostly in Subcollection I, Series I. In this series, see item II(2A5), containing correspondence from P.G. Downes to Speck regarding Cree in Quebec. See item II(2F3), which includes notes from A. irving Hallowell to Speck regarding field work visiting Sweet Grass Cree, mentioning attitude of Cree to Leonard Bloomfield. Item II(4B9c) contains Speck's field notes on the Mistassini band, including notes on relationship between Cree and Montagnais languages, as well as museum specimens. Item II(2G1) includes Naskapi names in Cree syllabary; the Lord's Prayer in Cree; miscellaneous syllabary Cree words, and images of 79 pictographs. In Subcollection I, Series II, see correspondence with Claude Schaeffer regarding Rocky Boy Cree, and correspondence with Paul A. W. Wallace regarding Cree tales (Wissakutchek) collected by Edward Ahenakew in Alberta. In Subcollection I, Series III, there are 4 "Cree" photograph folders containing approximately 60 photographs. See also "Naskapi films," located in Subcollection II, Series IV, Photographs and Video, which includes some footage of some Cree people.